The Memorable Thoughts of Socrates - Xenophon, 432 BCE-351? BCE; Morley, Henry, 1822-1894; Bysshe, Edward, active 1702-1712 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Memorable Thoughts of Socrates" by Xenophon is a collection of Socratic dialogues written after 371 BC. This work presents Xenophon's defense of his teacher Socrates, who faced charges of impiety and corrupting youth in Athens. Through short episodes and conversations, Xenophon portrays Socrates offering practical wisdom to friends and fellow Athenians, demonstrating his piety, self-control, and beneficial influence. The work significantly shaped Cynic and Stoic philosophy in ancient times. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Memorabilia_(Xenophon)
Release date is 2006-01-10
David Price
Keywords: Socrates, 470 BC-399 BC